2016
DOI: 10.1111/crj.12512
|View full text |Cite
|
Sign up to set email alerts
|

Association between fractional exhaled nitric oxide (FeNO) cutoff values (25 ppb) and risk factors of cough

Abstract: The cutoff values of FeNO (≥25 ppb or <25 ppb) are useful for etiological detection of cough with high sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The higher predictive ability was detected at FeNO >50 ppb where the best cutoff point for total IgE was ≥350 (sensitivity 66.7%, specificity 63.6%). A recent study by Qian et al reported that FeNO 25 ppb had a significant correlation with serum IgE between 200 and <200 IU/mL level l. 27 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The higher predictive ability was detected at FeNO >50 ppb where the best cutoff point for total IgE was ≥350 (sensitivity 66.7%, specificity 63.6%). A recent study by Qian et al reported that FeNO 25 ppb had a significant correlation with serum IgE between 200 and <200 IU/mL level l. 27 …”
Section: Discussionmentioning
confidence: 95%
“…A study by Qian et al reported that FeNO 25 ppb significantly correlated with FEV 1 /FVC ratio ( p =0.032) 27 while a recent study carried out on 160 Korean school children with asthma being monitored a FeNO value ≥35 ppb synchronized with asthma exacerbation. FEV 1 /FVC ratio as well as FEF25%–75% was significantly less than baseline in these children.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…59,103 This lack of clear cut-off levels of FeNO for the etiological diagnosis of asthma, CVA and NAEB in chronic cough [105][106][107] limits its usefulness as a routine diagnostic modality and follow-up assessment tool for chronic cough and compels its validation in future studies. 59,62,108,109 In the upper airways, an abnormally low nasal nitric oxide (nNO) is reportedly a predictor of nasal polyposis in severe asthmatic patients even when blood eosinophils are normal or low. 100 Also, primary ciliary dyskinesia can present with chronic cough (sinopulmonary infections) and low nNO 110,111 which can be supplemented by other testing modalities.…”
Section: Not Fully Established (à)Vementioning
confidence: 99%